Impasses no acolhimento de crianças e adolescentes em situação de violência sexual por profissionais da Estratégia Saúde da Família - Vera Lúcia Mendes Trabbold (2012)
The term "Sexual Violence against Children and Adolescents" was used in this work to designate both forms classified as "Sexual Abuse" regarding classified as "Commercial Sexual Exploitation of Children and Adolescents." Sexual abuse includes erotic practices that do not involve commercial gain either for the author, or to the victim, as in commercial sexual exploitation. This type of violence includes the involvement of a child or adolescent, in some act or sexual play, which can be homo or heterosexual, to sexually satisfy the author of the act that is in stage of psychosexual development long before the children and adolescents. It is an erotic practice imposed on the child or adolescent by threat of physical violence or mental induction. Juvenile Sexual Violence, one of violence manifestation, was considered by the World Health Organization in 2001 as a public health problem. The violence, while not itself a public health issue, becomes a matter for the health because it affects the individual and collective health and involves the services sector for its prevention and treatment. Therefore, the service units are now called to respond to victims of injuries, physical and emotional trauma, and should be equipped themselves for it. The creation of the program Family Health Strategy (FHS), formerly called the Family Health Program (FHP), Ministry of Health, opens up possibilities for more concrete action Health Industry regarding the issue of violence, usually just treated as subject to policeforces. Understood as a gateway to the health sector, the ESF must approach teams and health services to the real needs of individuals and families, these being its main focus to address the complex issues of public health, including violence. Therefore, this study aimed to investigate the discursive practices of different professional teams entered in the Family Health Strategy of the city of Montes Claros / MG on the identification and management of cases of sexual violence against children and adolescents. It was an exploratory, qualitative study using in-depth interviews with physicians, nurses and community health workers, belonging to three teams of the Family Health Strategy of the city of Montes Claros MG. In analyzing the data, to support our research method, we use the concepts of "discourse", "statement", "discursive fonnation" and "discursive practices" based on the works of Michel Foucault. We analyzed the statements that appear in the speech acts of the Family Health Strategy professionals that are related to the discursive practices of sexual violence against children and youth. In addition, other concepts of the mentioned author contributed to the analysis of the subject. Psychoanalysis used some concepts that gave us subsidies to the question of human subjectivity within the multidimensionality of the phenomenon of sexual violence. We also avail ourselves of authors connected to the field of Public Health, characterized as a counterhegemonic movement aimed to critically review the sanitary Brazilian model, marked as a complex field of bioscience disciplines originating from areas of human and environmental, with the objective discussing the biomedical model of health regulations. The survey results indicated that the current model of Family Health Strategy care seems to be characterized by a conceptual transition, predominantly biotechnology paradigm on a more humanized care model. Despite having a professional speech humanized, there are few practical actions. The prevalent practice in relation to violence is to take care of the situation, without listening, based on ideal moralizing, without building the case, filing, without interdisciplinary or intersectional. Insecurity and lack of preparation to deal with the issue of sexual violence, in addition to overloading from too many demands on the service routine causes violence cases are discovered by professionals, but omitted and denied by a number of stmctural factors, cultural and subjective. Even though it is not mandatory notifications are made, and the cases are passed on to other agencies. There is an emphasis on curability procedures with few prevention and health promotion. There is a gap in Family Health Strategy services regarding adolescent. There is a concept by the Professionals regarding the commercial sexual exploitation of children and adolescents, particularly for adolescents, but the complexity involved in this issue and the lack of staff training, the cases end up being neglected and not reported, and actions are timely. We conclude that by several factors, including the lack of institutional support, there is a failure on the part of Family Health Strategy people relative to the cases of sexual violence against children and youth. Thus, the Family Health Strategy does not constitute an input door for such cases. There is a need for continuing education, clinical case with building the team through supervision, so that professionals feel more empowered to act in such cases.